1994
DOI: 10.1177/019262339402200505
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic Effects of a Novel Acyl-CoA: Cholesterol Acyltransferase Inhibitor in Cynomolgus Monkeys

Abstract: Company. 2800

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…The structure-activity relationship studies of the derivatives with substituents in the C-phenyl ring, which had an ndecyl residue at R 2 in the A-phenyl ring (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), indicate the following. Results for monomethyl-substituted compounds (31)(32)(33) demonstrated that a 4-methyl residue was very important in exhibiting a high level of hypocholesterolemic activity in vivo, while a 2-methyl or 3-methyl residue was not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure-activity relationship studies of the derivatives with substituents in the C-phenyl ring, which had an ndecyl residue at R 2 in the A-phenyl ring (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), indicate the following. Results for monomethyl-substituted compounds (31)(32)(33) demonstrated that a 4-methyl residue was very important in exhibiting a high level of hypocholesterolemic activity in vivo, while a 2-methyl or 3-methyl residue was not.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical development of ACAT inhibitors, however, has not been successful, 25,26) be- [27][28][29][30][31][32][33][34][35][36][37][38] Recently, ACAT has been classified into two isozymes, ACAT-1 and ACAT-2, and research suggests that they differ in terms of their distribution in the body. [39][40][41][42][43] Two reasons are believed to be involved in why the numerous ACAT inhibitors that have been developed thus far have not been clinically successful.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both these effects suggest the generally known risk of secretory diarrhea caused by malabsorp tion of dietary lipids and excess bile acids. Dominick et al (24,25) recently reported diarrhea! episodes in ACAT inhibitor-treated beagle dogs, but did not refer to this in detail.…”
Section: Discussionmentioning
confidence: 99%
“…A number of acyl coenzyme A:cholesterol acyltransferase inhibitors have been synthesized, and their pharmacological profiles were evaluated in animals and humans. However, several adverse effects such as adrenal toxicity (Vernetti et al, 1993;Reindel et al, 1994;Matsuo et al, 1996), diarrhea (Kashiwa et al, 1997), and hepatotoxicity (Ishi et al, 1994;Nakaya et al, 1994) and various elusive efficacies in humans (Harris et al, 1990;Hainer et al, 1994;Tardif et al, 2004) have been revealed, and none of these compounds has so far succeeded in clinical development. Pactimibe sulfate was selected as a clinical development candidate showing good oral absorbability and potent pharmacological effects in apolipoprotein Edeficient mice (Terasaka et al, 2007) and Watanabe heritable hyperlipidemic rabbits (Kitayama et al, 2006b) without showing significant adrenal toxicity even in dogs, the most sensitive animal species.…”
Section: Introductionmentioning
confidence: 99%